1995
DOI: 10.1046/j.1537-2995.1995.35595259149.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin as an inactivator of infectious viruses in blood components

Abstract: The apparent transfusibility of hypericin, taken together with the efficacy of the virucidal activity, the broad range of enveloped viruses affected, and the absence of adverse effects on stored red cells, may render hypericin useful for inactivation of infectious viruses in red cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…Importantly, it was reported that hypericin binds to human lipoproteins at high molar ratios (up to 467 and 14 moles per 10 4 Da of low-density lipoproteins (LDL) and high-density lipoproteins (HDL), respectively) (Lavie et al, 1995b). In contrast to human plasma, mouse plasma contains a high HDL/LDL ratio (Kessel and Woodburn, 1993), so that mainly the hypericin -HDL complex is formed in the bloodstream of mice (results not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, it was reported that hypericin binds to human lipoproteins at high molar ratios (up to 467 and 14 moles per 10 4 Da of low-density lipoproteins (LDL) and high-density lipoproteins (HDL), respectively) (Lavie et al, 1995b). In contrast to human plasma, mouse plasma contains a high HDL/LDL ratio (Kessel and Woodburn, 1993), so that mainly the hypericin -HDL complex is formed in the bloodstream of mice (results not shown).…”
Section: Discussionmentioning
confidence: 95%
“…We initially hypothesized a faster blood and liver clearance for the less lipophilic [ (10,12). As is the case for many other photosensitizers, hypericin has been found to associate mainly with lipoproteins and to a lesser extent other proteins in blood (6,13). In contrast to human plasma, mouse plasma has a higher ratio of HDL/LDL (14).…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of tumor accumulation of hypericin is not fully understood. It has been proposed by some authors (7,13) that the mechanism of its delivery to the tumor is by receptormediated endocytosis of lipoprotein bound drug. Van I]MIH as tumor diagnostic agent will involve SPECT imaging during which images will be registered at different time points with the aim of finding the optimal time at which the best target to non-target ratio is reached.…”
Section: Discussionmentioning
confidence: 99%
“…The strong interaction between HY and HSA does not prevent HY from exerting its photobiological action, suggesting a reversible interaction of HY with HSA [13,14].…”
Section: Hypericum Perforatum L (H Perforatum)mentioning
confidence: 95%